An evaluation of eating attitudes in patients with migraine and tension type headache - İnanç, Yılmaz; Orhan, Fatma Özlem; Erdoğan, Ayşegül; Gökçe, Mustafa; İnanç, Yusuf; Özyurt, Erdem (The European Research Journal, 2019)
Objective: The aim of the study was to examine eating attitudes in patients with migraine and tension type headache.Methods: The study included 89 patients diagnosed with migraine according to the International Headache Society (IHS) 2004 criteria, 87 patients with tension type headache and 89 healthy volunteers matched in terms of age, gender and education level. A detailed neurological examination was made of all the participants and the Eating Attitudes Test (EAT), the Beck Anxiety Inventory (BAI) and the Beck Depression Inventory (BDI) were applied.Results: In the comparisons of the EAT points, 23 of the tension type headache group and 18 of the migraine group were in the EAT ≥ 30 group, which was a statistically significantly higher rate compared to the control group (p = 0.099). The mean BDI points and the mean BAI points of both the migraine and the tension type headache groups were statistically significantly higher than those of the control group (p = 0.001 and p = 0.002, respectively). Conclusions: The results showed impairment in the eating attitudes of patients with migraine and tension type headache compared to the control group. When it is considered that some foodstuffs trigger headaches, eating disorders or impaired attitudes to eating become important.